Quantitative Analysis of Qualitative Data on Factors Affecting College Students' Motivation to Exercise - Horii, Daisuke; Kaneda, Hiratoshi; Okuda, Enji; Sugiyama, Yoshio (Advances in Social Sciences Research Journal, 2024)
Various factors affect differences in the willingness to exercise. Most studies on motivation to exercise clarify its relevance and potential causal relationships using questionnaire surveys and analyze the constructed models. Therefore, by analyzing both conventional questionnaire surveys and freeform sentences, this study attempts to derive certain trends in phenomena that were overlooked when the questionnaires were developed. We conducted a questionnaire survey of 256 university students’ motivation to exercise, and further examined factors that may increase motivation to exercise using text mining and correspondence analysis. Consequently, when creating categories based on appearance frequency, teachers, fathers, mothers, friends, supervisors, coaches, and seniors were extracted as individuals who may increase or decrease motivation to exercise. The results of the content analysis confirmed that the influence provided by fathers included offering guidance and actual exercise experience, while mothers were mainly engaged in supportive relationships; furthermore, rivalry between siblings participating in exercise together was detected. Praising and scolding were also found to be important in increasing the motivation to exercise. The influence on the motivation to exercise was considered to change depending on how the individual perceives their environment.